Prevalence, risk factors and echocardiographic predictors of pulmonary hypertension in systemic lupus erythematosus: towards a screening protocol - Jorge Álvarez Troncoso; Clara Soto Abánades; Ángel Robles-Marhuenda; Sergio Alcolea Batres; María Fernández Velilla Peña; Santiago Jiménez Valero; Raquel Sorriguieta Torre; Juan José Rios-Blanco (RMD Open)
Background Systemic lupus erythematosus (SLE) significantly affects the lungs and heart, and pulmonary hypertension (PH) is a severe manifestation that leads to considerable morbidity and mortality.Objectives We aimed to determine the prevalence and risk factors of probable SLE-PH, assess the main echocardiographic predictors and develop a potential screening strategy.Methods A prospective single-centre study was conducted on 201 patients with SLE who underwent transthoracic echocardiography. Patients meeting PH criteria were referred for right heart catheterisation (RHC).Results Among patients, 88.56% were women, 85.57% were of Spanish origin and 43.78% had structural heart disease. Out of these, 16 (7.96%) had intermediate or high probability criteria for PH according to European Society of Cardiology (ESC) 2022. Six RHCs confirmed PH with a prevalence of 2.99% for SLE-PH and 1.99% for SLE-pulmonary arterial hypertension (PAH).Key risk factors Key risk factors included age, cardiorespiratory symptoms, serositis, anti-Ro, cardiac biomarkers and altered pulmonary function tests (PFTs). PH was linked to a higher Systemic Lupus International Collaborative Clinics/American College of Rheumatology Damage Index (SDI) (mean SDI 4.75 vs 2.05, p<0.001) and increased mortality risk in a 2-year follow-up (12.50% vs 1.08%, p=0.002).Conclusion In our cohort, 7.96% of patients with SLE had an intermediate or high PH probability. By RHC, six patients (2.99%) met the ESC/European Respiratory Society criteria for PH and four (1.99%) for PAH. The main risk factors were older age, cardiorespiratory symptoms, serositis, anti-Ro, cardiac biomarkers and altered PFTs. PH was a severe SLE complication, suggesting the need for earlier diagnosis through data-driven screening to reduce associated morbidity and mortality.